2012
DOI: 10.1182/blood-2011-03-342055
|View full text |Cite
|
Sign up to set email alerts
|

CD62L− memory T cells enhance T-cell regeneration after allogeneic stem cell transplantation by eliminating host resistance in mice

Abstract: A major challenge in allogeneic hematopoietic cell transplantation is how to transfer T-cell immunity without causing graftversus-host disease (GVHD). Effector memory T cells (CD62L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…These data indicated that T cell expansion was severely inhibited in both T EM -like cell and T EM recipients during GVHD at least at the peak of naïve T cell expansion. Because allospecific T EM are able to proliferate and expand in response to alloantigen as indicated in the mixed lymphocyte reaction assay (Figure 3C), the in vivo T cell expansion data suggested that, similar to memory T cells from unprimed donors (22, 23), allospecific T EM also mediated an abortive alloresponse after hematopoietic stem cell transplantation. Cytokine storm is a downstream cascade after T cell activation and clonal expansion during GVHD (24).…”
Section: Resultsmentioning
confidence: 91%
“…These data indicated that T cell expansion was severely inhibited in both T EM -like cell and T EM recipients during GVHD at least at the peak of naïve T cell expansion. Because allospecific T EM are able to proliferate and expand in response to alloantigen as indicated in the mixed lymphocyte reaction assay (Figure 3C), the in vivo T cell expansion data suggested that, similar to memory T cells from unprimed donors (22, 23), allospecific T EM also mediated an abortive alloresponse after hematopoietic stem cell transplantation. Cytokine storm is a downstream cascade after T cell activation and clonal expansion during GVHD (24).…”
Section: Resultsmentioning
confidence: 91%
“…Here we discuss only recent informative updated trials and reports (Table 3); data reported between 2012 and 2013) regarding the promotion of immune reconstitution, particularly in haploidentical transplantation settings [53,65,69,107].…”
Section: Strategies To Improve Immune Reconstitution After Haploidentmentioning
confidence: 99%
“…This procedure was performed according to a previously publication from our laboratory [16]. Briefly, BALB/c nude mice were first irradiated with a lethal dose of radiation (8.5 Gy).…”
Section: Methodsmentioning
confidence: 99%